Fertirrigation for vegetables grown in greenhouses - Putti, Fernando Ferrari [UNESP]; Gabriel, Camila Pires Cremasco [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Reis, André Rodrigues dos [UNESP] (Korean Society for Agricultural Machinery, 2014)
Purpose: Concerns over the quantity of available freshwater for agriculture have triggered the development of technologies intended to increase efficiency of water use, especially with regard to irrigation. A new technique called fertirrigation has been developed to use the same irrigation equipment for fertilization. Methods: Since the above-mentioned technique requires care during installation and use on farms, current analysis focuses on some of its characteristics. Results: High uniformity irrigation systems provide the best distribution of fertilizers, especially when used in combination with drip irrigation or micro-aspersion. The factors purity, compatibility, acidification, salinity, and solubility should be taken into account. Conclusions: Fertirrigation provides a significant increase in productivity as it allows for highly controlled nutrient application during the entire growing season. However, it may cause serious problems if misused or overused.
Keywords: Economic; Fertirrigation; Irrigation; Production; Quality